Biological Activities of Hominis Placenta Herbal Acupuncture prepared by Hydrochloric Acid Hydrolysis - Geun-young Seo; Sung-won Lee; Sung-joo Park; Sung-chul Kim; In-chul Sohn; Sung-yeoun Hwang; Seong-hun Ahn (Korean Pharmacopuncture Institute, 2010)
Reactive Oxygen Species(ROS) are continuously produced at a high rate as a by-product of aerobic metabolism. Since tissue damage by free radical increases with age, the reactive oxygen species(ROS) such as hydrogen peroxide(H2O2), nitric oxide(NO). Several lines of evidence provided that ROS appears to cause to develop aging-related various diseases such as cancer, arthritis, cardiovascular disease. In this study, we have conducted to investigate the biological activities of Hominis Placenta Herbal Acupuncture by measuring total polyphenol content, DPPH radical scavenging, ABTS radical scavenging, Superoxide dismutase(SOD)-like activity, Nitrite scavenging ability in vitro. The total polyphenol contents of Hominis Placenta Herbal Acupuncture was 24.6㎖/㎖. Elctron donation ability on DPPH was 49.4%. The 2,2'-azinobis-3-ehtlbezothiazoline-6-sulfonic acid radical decolorization (ABTS) was 50.01%, similar to the DPPH free radical scavenging. The superoxide dismutase (SOD)-like activities of hominis placenta herbal acupuncture was 50.876%. The nitrite scavenging abilities at pH 1.5, pH 3.0, pH 6.0 were 52.8%, 29.4%, 15.4%, respectively; these abilities decreased as pH increased. We conclude that Hominis Placenta Herbal Acupuncture may be useful as potential sources of antioxidant.